Medellín: uma criativa “recepção” do concílio - Tavares, Sinivaldo Silva (Revista Eclesiástica Brasileira, 2008)
Na ocorrência dos 40 anos da Assembléia Geral do Episcopado latino-americano celebrada em Medellín, o A. salienta a singularidade deste importante evento eclesial. Convocada com o intuito de aplicar o Vaticano II à realidade eclesial do Continente, Medellín operou uma verdadeira re-interpretação do mesmo a partir do desafiador e fecundo contexto latino-americano. O A. caracteriza esse fato como “uma autêntica recepção criativa”. A partir, portanto, das angústias, das esperanças e dos anseios dos pobres do Continente latino-americano, esta peculiar “recepção” conferiu densidade humana e evangélica às melhores intuições do Concílio. O A. conclui convocando-nos a reavivar a memória de Medellín face aos urgentes e interpelantes desafios do tempo presente. Abstract: On the 40th anniversary of the General Assembly of the Latin American Bishops held in Medellin, the Author emphasizes the singularity of this important ecclesial event. Summoned with the objective of applying the Vatican II ideas to the Continent’s ecclesial reality, Medellin carried out a true re-interpretation of the Council having as a starting point the challenging and prolific Latin American context. The Author considers this fact “an authentic creative reception”. Therefore, starting from the anxieties, hopes and longings of the Latin American Continent’s poor, this specific “reception” granted human and evangelical depth to the Council’s best insights. The Author concludes by inviting us to relive the memory of Medellin in view of the urgent and questioning challenges of our times.